Overview of the legislation of the Republic of Serbia regarding the Second Victims Phenomenon at community pharmacists - Zimonjić, Ivana; Marinković, Valentina; Odalović, Marina (Archives of Pharmacy, 2022)
Following challenges in the global environment, technologies in pharmaceutical care, pressures to performance and timelines, community pharmacists are facing with impact of adverse healthcare outcomes on their health and wellbeing, described in literature as second victims phenomenon. The aim of this paper is review of the national regulations in protection of pharmacists in traumatic situations during the healthcare. From January 2022 to May 2022, the websites of the Ministry of Health, the Pharmaceutical Chamber, the Paragraph, and the Legal Information System were searched using the keywords: patient safety, healthcare workers safety, regulations, pharmacists. The results showed that regulations protect patients, while healthcare workers, as second victims, are not protected. Patient safety is regulated through Law on Health Care, Law on Health Documentation and Records in Health, Ordinance on reporting, collecting, and monitoring adverse reactions to medical devices. The protection of healthcare workers is regulated from the aspect of working conditions, including interpersonal relations, through the Law on Safety and Health at Work, Law on Prevention of Abuse, Ordinance on Internship and Professional Exam of Health Workers and Associates, GPP Guide and Ethical Code of Pharmacists of Serbia. On the website of the Pharmaceutical Chamber, there is a section “Report violence”, which allows to fill the Questionnaire on violence against healthcare workers. After considering all the aspects, it is conluded that the protection of pharmacists and other healthcare workers in this context is not regulated, phenomenon is new and there is a room for discussion in adopting future regulations.